2011
DOI: 10.1071/py10017
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to recruitment of professionals into a general practice childhood obesity program

Abstract: Recruiting general practitioners to take part in research in primary care is important and challenging. This paper describes the process, barriers and achievements experienced by a research team whilst recruiting Divisions and general practitioners (GPs)/practices into a project related to management of obesity in children, which used Breakthrough Series methodology in the intervention arm. The research team chose to recruit GPs through Divisions of General Practice, because of the existing positive relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Amongst those FPs who met the recruiter, the predominant explanation for refusal was lack of time, a reason commonly cited in the literature [8,[16][17][18][19][20][21][22]. In other studies remuneration has been shown to play a positive role in physician recruitment; however, it was not reported as a factor influencing our FP sample [15,[22][23][24][25][26][27][28].…”
Section: Recruitment Of Physiciansmentioning
confidence: 56%
See 1 more Smart Citation
“…Amongst those FPs who met the recruiter, the predominant explanation for refusal was lack of time, a reason commonly cited in the literature [8,[16][17][18][19][20][21][22]. In other studies remuneration has been shown to play a positive role in physician recruitment; however, it was not reported as a factor influencing our FP sample [15,[22][23][24][25][26][27][28].…”
Section: Recruitment Of Physiciansmentioning
confidence: 56%
“…Of the 400 randomly selected FPs ( (38), not in office family practice (54), on leave (31), not actively practicing (31), did not have patients fitting study profile (13), remote from the research centre(3), for whom contact information was unavailable (1); ** No time (19), not interested in the project (9), never participate in research (5), finds remuneration for participation, insufficient (1), satisfied with present approach to care (1), patients with language barriers (1), no reasons given (7).…”
Section: Recruitment Of Physiciansmentioning
confidence: 99%
“…While low intervention intensity offers one explanation for low HKC uptake, other explanations include implementation barriers and/or reporting difficulties 26 . Low uptake of the HKC has been reported previously 27 .…”
Section: Discussionmentioning
confidence: 86%
“…Time constraints due to other commitments like audits and mass vaccinations can often hinder doctors' participation in research (Asch et al 2000;Rosemann and Szecsenyi 2004;Minas et al 2005;GoodyearSmith et al 2009) Australian GPs do not rate financial rewards as a reason to join a research project; however, financial incentives can support a practice's loss of time. There are also project-related and topic-related reasons why GPs do not participate, such as an overly complex research design or a disease area that is considered too sensitive, such as childhood obesity (Jones et al 2011(Jones et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have been urged to incorporate evaluations of recruitment strategies into study appraisals in an effort to obtain more evidence about the effectiveness of recruitment methods (Watson and Torgerson 2006). Such evaluations can help researchers obtain information regarding recruitment for studies similar to theirs (Jones et al 2011).…”
Section: Introductionmentioning
confidence: 99%